Exercise improves cognitive dysfunction and neuroinflammation in mice through Histone H3 lactylation in microglia - Han, Hao; Zhao, Yawei; Du, Junda; Wang, Sushan; Yang, Xuehan; Li, Weijie; Song, Jiayi; Zhang, Siwei; Zhang, Ziyi; Tan, Yongfei; Hatch, Grant M.; Zhang, Ming; et al. (Immunity & ageing, 2023)
Background Exercise is postulated to be a promising non-pharmacological intervention for the improvement of neurodegenerative disease pathology. However, the mechanism of beneficial effects of exercise on the brain remains to be further explored. In this study, we investigated the effect of an exercise-induced metabolite, lactate, on the microglia phenotype and its association with learning and memory. Results Microglia were hyperactivated in the brains of AlCl 3 /D-gal-treated mice, which was associated with cognitive decline. Running exercise ameliorated the hyperactivation and increased the anti-inflammatory/reparative phenotype of microglia and improved cognition. Mice were injected intraperitoneally with sodium lactate (NaLA) had similar beneficial effects as that of exercise training. Exogenous NaLA addition to cultured BV2 cells promoted their transition from a pro-inflammatory to a reparative phenotype. Conclusion The elevated lactate acted as an “accelerator” of the endogenous “lactate timer” in microglia promoting this transition of microglia polarization balance through lactylation. These findings demonstrate that exercise-induced lactate accelerates the phenotypic transition of microglia, which plays a key role in reducing neuroinflammation and improving cognitive function.